THE PARTICIPATION SYSTEM OF WASTE PRODUCTS INTEGRATION MANAGEMENT OF COMMUNITY IN THE CENTRAL AREA - Suksai, Samphan (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2020)
The objectives of this article are to 1) analyze the fundamental problems of integrated waste management participation of the communities in the central provinces area and 2) to build a model of a system of integrated waste management participation of the communities in the central province area. This research deploted mix-research method with the survey sample of 400 people, 17 key informants / person and 25 photos / specialist in the field were obtained by the specific termination method. The research instruments were 1) questionnaire; 2) in-depth interview form and 3) group discussion record. Statistical data analysis was done by using a computer program and used Content Analysis Technique for context analysis. The results of this research found that: 1. Fundamental problems of integrated waste management participation of the communities in the central provinces area found that the main problem is the waste management problem followed by the waste problem in the community that is caused by the ignorance of public waste management whie the participatory approach found that all people should be trained in waste management to raise waste management awareness and conduct continuous assessment of the waste situation. 2. The model of the integrated community waste management system of the communities in the central provinces area was found to have 3 important goals: 1) clean communities, 2) clean Thai localities, and 3) healthy people. The management principle is the establishment of a waste recycling bank, encouragements for waste management, cultivating of a sense of responsibility in the community, constant supervision and participation in determining direction and solving problems together.